Leisure's Legacy : Challenging the Common Sense View of Free Time - Stebbins, Robert A. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book illustrates how leisure, as with other complex ideas that hold currency in today's world, suffers at the level of common sense, due to a combination of oversimplification, moral depreciation, and even lack of recognition. Leisure's modern legacy is both profound and immense, as a product of approximately 45 years of steady research, application and theory development. The common sense view of free-time activities, therefore, can and should be challenged. Stebbins provides this confrontation by tackling four particular themes: that gatekeepers within the institutions of higher education and funding agencies for research often fail to attach adequate resources to the idea of leisure; that the general population are guided by certain common sense definitions and largely unaware of how an informed view of free time could be beneficial; that practitioners within certain fields continue to refuse to engage with the idea of leisure despite its benefit for their clients; and that the weak reception of the science of leisure within mainstream social sciences suggests a similarly warped understanding of how people use their free time. Leisure's Legacy will be of interest to scholars of Leisure Studies and all those wishing to learn more about the vital importance of leisure in modern Western society.
Keywords: Social sciences.; Religion and culture.; Social sciences -- Philosophy.; Sports -- Sociological aspects.; elektronické knihy; electronic books